EFEK SUPLEMENTASI OMEGA-3 PADA PENDERITA ARTRITIS REUMATOID - Reviana Christiani; Sri Martuti; Susilowati Herman (Persagi, 1999)
Effects of Omega-3 Supplementation on Patients With Rheumatoid Arthritis.A study on omega-3 supplementation was conducted to women of 55-90 years old with active rheumatoid arthritis who stay at home for elderly (in six nursing home) in Bogor. The objective of this study is to see the effects of omega-3 supplementation on patients with active rheumatoid arthritis. Sixty subjects (respondents) were devided into two groups. The first group, 30 respondents, were given an omega-3 capsuls (180 mg EPA and 120 mg DHA) every day for two months; the second group, also 30 respondents, were given placebo capsules (equal). Data collected including identity of respondents, anthropometric, clinical status, radiology (rontgen), and blood sample analysis (LED and ARF). The results of this study showed that omega-3 supplementation proportionally decreased the quantity of patients with morning stiffness significantly, decreased the quantity of patients with joint swelling (not significant), failed inreducing the quantity of patients with joint pain, and failed in changing the value of RF (from + to -) of patients. The omega-3 supplementation on patients with active rheumatoid arthritis also failed in decreasing the average of LED of the patients, and failed in changing the result of rontgen.Keywords: rheumatoid arthritis, EPA & DHA omega-3, supplementtaion, elderly.